Tectonic SAM: Exact, Out-of-Core, Submap-Based SLAM - Kai Ni; Steedly, D.; Dellaert, F. (Proceedings 2007 IEEE International Conference on Robotics and Automation, 2007)
Simultaneous localization and mapping (SLAM) is a method that robots use to explore, navigate, and map an unknown environment. However, this method poses inherent problems with regard to cost and time. To lower computation costs, smoothing and mapping (SAM) approaches have shown some promise, and they also provide more accurate solutions than filtering approaches in realistic scenarios. However, in SAM approaches, updating the linearization is still the most time-consuming step. To mitigate this problem, we propose a submap-based approach, tectonic SAM, in which the original optimization problem is solved by using a divide-and-conquer scheme. Submaps are optimized independently and parameterized relative to a local coordinate frame. During the optimization, the global position of the submap may change dramatically, but the positions of the nodes in the submap relative to the local coordinate frame do not change very much. The key contribution of this paper is to show that the linearization of the submaps can be cached and reused when they are combined into a global map. According to the results of both simulation and real experiments, Tectonic SAM drastically speeds up SAM in very large environments while still maintaining its global accuracy.